RELATION OF AUTHORITY INTERVENTION POWER IN THE ONLINE PROSTITUSION IN KOMPAS.COM - Zaqiyah Lailatul Farihah; Wikanengsih Wikanengsih (IKIP Siliwangi, 2019)
The issue of online prostitution has lately been discussed. The involvement of the artists was allegedly a trigger for the crowd over the discourse on the reporting of online prostitution. This research focuses on daily reporting of the compass regarding the discourse of online prostitution. The research method used is a qualitative approach with qualitative-descriptive analysis techniques. Critical Discourse Analysis which refers to the perspective of Foucault’s power relations as a research knife. The results of the study show that the rise of artists involved in online prostitution is assumed to be the demand of their image which has been formed by the media as people who must appear perfectly.